A influência do modo de organização na compreensão de hipertextos - Marcelo Cafiero Dias (2008)
The aim of this reseach is to evaluate readers comprehension of different kinds of hypertexts home page and menu organization. Guided by reading theories proposed by Kleiman (1992, 1993) and Smith (1993) and by research presented by Rouet et al. (1996) and Coscarelli (2005a), we work on the hypotheses that the imagetic organization would conductreaders to produce a satisfactory mental representation of the hypertext and to understand it better then the verbal organization, given that it seems to have more clues that could guide the reading hypothesis. We presented the same hypertext in three different formats - verbal, image and mixed organized - to readers at the last two years of elementaty school. First, we asked the subjects about their reading hypotheses and, after reading the text, we evaluated their comprehension through questions related to several reading abilities. The results suggestthat imagetic and mixed versions guided readers to elaborate reading hypotheses more likely to be correct. However, quantitative data of textual comprehension questions indicates that hypertext verbal version readers comprehend the text better and that there is no significant difference between the text versions in other evaluated abilities. A closer analysis, on other hand, suggests that verbal and mixed versions readers navigate more efficiently and that verbal version readers could find information in text better. A qualitative analysis, guided by reading theories and by Mental Spaces and Conceptual Integration Theory (FAUCONNIER;TURNER. 1998, 2002), shows that verbal version readers used more contextual information to build their reading hypotheses and were also more capable of rebuild them, when it was necessary, after reading the hypertext. This lead us to observe that a hard time building a reading hypothesis for the text lead this version readers to a more active participation at the experiment. The experimental results and analysis uide us to conclude that verbal organization of a hypertext seems to suggest better its structure and, thus, readers comprehend it better, however the more efficient hypertexts organization depends on the authors prior objectives.